RANCANG BANGUN PORTAL WEB AKADEMI MANAJEMEN INFORMATIKA DAN KOMPUTER (AMIK) INDONESIA BANDA ACEH - Junaidi, Junaidi (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
This study aims to design a web portal Academy of Information Management andComputer (AMIK) Indonesia. Presentation of information on the Academy of ManagementInformation and Computer Indonesia has yet to use web portal. Therefore, the requiredinformation portal that can be used as an alternative media on campus AMIK Indonesiaintroduced properly and quickly. In building a web portal, the writer uses a programmingdevice web-based open source PHP and MySQL database. The resulting web portal can beused to access a variety of information and news about the activities of lectures at theAcademy of Management Information and Computer Indonesia. Thus information can beseen by all the people who need the information online.Keywords : AMIK Indonesia, web portals, information